Rus arşiv kaynakları ışığında 1923-1939 arası Türk-Sovyet ekonomik ilişkileri - Erdal Bilgiç (My University, 2019)
Bu tezin amacı iki savaş arası dönemde Sovyetler Birliği ve Türkiye arasındaki ilişkileri ekonomik yönden incelemektir. İki ülke arasındaki ekonomik ilişkilerin yönünü belirleyen, Sovyet Ticaret Kurumlarının Türkiye'deki örgütlenme şekli olmuştur. Sovyet dış ticaret tekelinin dünya ekonomik sistemi içinde tanınması kolay olmamıştır. Bu yüzden Sovyetler Birliği dış ticaretini yöneten bürokratlar hem ülke içinde hem de ülke dışında birçok değişik metodu uygulamak zorunda kalmıştır. Ülkenin ithalat ve ihracatının eksiksiz ve zamanında gerçekleşmesi için tröstler, sendikalar ve hatta anonim şirketler beraber çalışmışlardır. Sovyetler Birliğinin dış ticaret tekelini aşmak için kurduğu anonim şirketlerin yer aldığı ülkeler içinde Türkiye'de yer almaktadır. Arkos ve Russotürk isimli iki adet şirketten ilki daha mütareke dönemlerinde İstanbul'da çalışmaya başlamıştır. Russotürk ise Türk burjuvazisinin yatırımlarını çekerek Sovyet Dış Ticaret Bakanlığının ortaklığında kurulmak istenmiştir. Arkos'un altında bağımsız olarak örgütlenen Petrol Sendikası ise Sovyetlerin cumhuriyetin henüz ilk yıllarında ihracatını önemli bir kısmını yapmayı başarmıştır. Kafkaslar Üzerinden Ticaret Yapan Kurum ise Sovyetlerin Doğu Anadolu'daki ticari faaliyetlerini örgütleyen Tiflis merkezli başka bir kuruluştur. Bahsi geçen kurumların hikayesi literatürde alışılagelen Sovyetlerin Kurtuluş Savaşında yapmış olduğu yardımlar ve İkinci Dünya Savaşına kadar uzanan uluslar arası ilişkiler literatürünün dışında alternatif bir tarih anlatısı sunmaktadır. 1927 yılında imzalanan ticaret anlaşması iki ülke arasındaki ekonomik ilişkilerin seyrini olumlu yönde değiştiren bir hamle olmuştur. Sovyetler Birliği böylelikle Türkiye'deki anonim şirketlerini ve onların altında çalışan diğer ticaret kurumlarını Ticaret Temsilciliği adı altında birleştirmiştir. Böylelikle 1930'lar boyunca Sovyet-Türk ekonomik ilişkilerini geliştiren bir yapı halini almıştır. İki ülke arasındaki ilişkileri iktisat tarihinin konusu olarak ele alan bu çalışmada Türkiye'de iki savaş arası dönemde görev yapmış Sovyet ticaret kurumlarının rolü, amaçları, değişimleri ve ticaret rakamları tartışılmıştır.

The aim of this thesis is to analyze the relations among the Turkish Republic and the Soviet Union between the two World Wars. The organizational form of the Soviet trade institutions is the main dynamic that determines the direction of economic relations between the two countries. It was not a trivial task for the global economic system to accept and acknowledge the Soviet Union’s foreign trade monopoly. Therefore, the bureaucrats that administer the foreign trade of the Soviet Union had to utilize many different methods both domestically and internationally. Many trust funds, industrial unions and even joint stock companies collaborated in order to maintain the imports and exports of the country in a complete and punctual manner. Turkey belongs to a list of countries that the Soviet Union established joint stock companies to surpass the foreign trade monopolies. Arkos and Russoturk are the two joint stock companies and the former one started its operations in Turkey even during truce period. Meanwhile, Russoturk was tried to be established as a joint venture of Ministry of Soviet Foreign Trade and Turkish bourgeois. The Petroleum Syndicate, which was organized independently under Arkos administration, achieved a major share of the Soviet Union’s export in the first years of the Turkish Republic. The Institution that engaged in trade operations through Caucasian border is one of the Tbilisi based establishments that organized the commercial activities of Soviets in East Turkey. The story of above-mentioned institutions provides an alternative historical narrative other than the usual tale of assistance of Soviets during the War of Independence and the texts that cover the international relations of the two countries up until the World War II. The bilateral trade agreement that was signed in 1927 was a move that affected the economic relations of the two countries positively. Through this agreement, the Soviet Union united its joint stock companies in Turkey and the other establishments that operated consequent to them under an umbrella institution called Trade Agency. Thus, this institution became an establishment that promoted the economic relations of Turkey and the Soviet Union throughout 1930s. In this study, where the relations of the two countries are covered in the context of economic history, the status, goals, conversions and trade amounts of the Soviet trade institutions, which operated between the two World Wars in Turkey, are analyzed and discussed.
Keywords: Dış Ticaret Russia; Economy; Ekonomi; Finance; Foreign Trade; International economic relations; Maliye; Rusya; Soviet Union; Sovyetler Birliği; Turkey; Turkey-- Russia; Türkiye; Uluslararası ekonomik ilişkiler